Cultural and Pragmatic Aspects of Compliment Responses: A Study of Indonesian EFL Learners - Merry Sylvia; Yetti Zainil (AL-ISHLAH: Jurnal Pendidikan, 2025)
Compliment responses play a vital role in academic communication as indicators of pragmatic competence and cultural values. In multilingual contexts such as English and Minangkabau, they further reflect how students negotiate cultural identity through language use. This study examined university students’ compliment responses in English and Minangkabau using Searle’s (1969) speech act theory—focusing on expressive acts—and Chung’s (2010) classification of strategies: acceptance, amendment, non-acceptance, and combination. A descriptive qualitative approach was employed. Data were collected through a Discourse Completion Test (DCT) administered to 20 participants and follow-up interviews with 10 of them to explore the reasoning behind their choices. Analysis revealed that students used ten distinct strategies across both languages. The acceptance strategy, particularly through appreciation tokens, was most frequently employed, accounting for 66.7% of responses in English and 52.9% in Minangkabau. These results suggest that while students tended to accept compliments, they also adapted their responses to align with sociocultural expectations in each language. The findings indicate that students’ pragmatic competence is shaped by both linguistic proficiency and cultural norms. Their bilingual practices reflect an effort to balance modesty with acknowledgment, reinforcing their cultural identity in communicative exchanges. Integrating cultural awareness into English as a Foreign Language (EFL) instruction is essential to develop learners’ pragmatic competence and promote effective intercultural communication.